Cyclic Nucleotide Phosphodiesterases and Human Arterial Smooth Muscle Cell Proliferation - Rybalkin, Sergei D.; Bornfeldt, Karin E. (Thrombosis and Haemostasis, 1999)
Smooth muscle cells (SMCs) in the arterial wall are normally found in a contractile, nonproliferative state. These SMCs are continuously exposed to agents that elevate cyclic AMP (cAMP) and cyclic GMP (cGMP), such as prostacyclin and nitric oxide (NO) released from the endothelium. Both cAMP and cGMP potently inhibit SMC proliferation by antagonizing major signaling pathways induced by growth factors, such as platelet-derived growth factor. Different forms of injury to the endothelium result in proliferation of the SMCs and can develop into atherosclerosis, restenosis, or arterial thickening associated with neonatal pulmonary hypertension. In human adult aorta, cAMP and cGMP levels are tightly regulated by synthesis and degradation. The latter is mediated by at least two different cAMP phosphodiesterases (PDEs), PDE3 and PDE4, and three different PDEs that degrade mainly cGMP, PDE1A, PDE1B, and PDE5. Strikingly, expression of a new PDE that degrades both cAMP and cGMP, PDE1C, is markedly induced in proliferating SMCs from the same aorta in culture, whereas its expression is nondetectable in contractile aorta. We propose that, for a human arterial SMC to be able to efficiently proliferate, and perhaps even to undergo a phenotypic change from a quiescent to a proliferative phenotype, it has to efficiently degrade inhibitory cAMP and cGMP. In human SMCs, PDE1C is induced to degrade these cyclic nucleotides. Understanding the role of PDE1C in SMC proliferation may provide the basic information necessary for development of highly specific PDE1C inhibitors that target proliferating SMCs in cardiovascular disease.